The Role of Authentic Leadership in Improving Employee Performance Through Individual Creativity - Dutahatmaja, Angga (International Conference On Economics Business Management And Accounting (ICOEMA), 2022)
The purpose of this study is to identify the relationship between authentic leadership in improving individual performance through trust. Individual employee performance needs to be improved to achieve the goals of a company, so it takes creativity to find new ideas to run the company’s business processes and is supported by the role of an authentic leader in running a company. The method used in this study is a meta-analysis of 20 previous studies that discuss authentic leadership, individual creativity and individual performance. The results show that authentic leadership and individual creativity affect employee performance. Individual creativity can mediate the relationship between authentic leadership and individual performance.